Peranan Akuntansi Pertanggungjawaban Sebagai Alat Pengendalian Biaya Produksi Kelapa Sawit Pada PT. Perkebunan Nusantara IV Regional 2 - Batu, Angel Natasya Lumban; Sinurat, Mangasa; Sihombing, Halomoan (Jurnal Ekonomika Dan Bisnis (JEBS), 2025)
When the research was conducted, that the realization was higher than the budget (RKAP) on production costs due to the price (Rp) / kg in the realization was higher or more than the price (Rp) / kg in the budget, so that there could be a difference between the budget and the realization of palm oil production costs for the period 2022 which could have an impact on production cost control. Therefore, the role of responsibility accounting is important in achieving company goals and also controlling palm oil production costs in a company, with the role of responsibility accounting, companies can set clear cost standards and identify the causes of cost differences that occur, such as unprofitable cost differences where the realization of production costs is greater than the production cost budget. The study aims to determine and analyze the role of accountability accounting as a means of controlling palm oil production costs at PT Perkebunan Nusantara IV Regional 2 Period 2022. This research uses a qualitative descriptive approach with data obtained through documentation studies and interviews conducted. Variance analysis technique is used to compare actual costs with budget costs, both in terms of price and quantity, both indirect costs and direct costs. The results showed that in terms of price, some costs experienced unfavorable variance, while in terms of quantity showed favorable variance. The implementation of responsibility accounting has gone well and helps control costs. From these results it is recommended that the company can improve control of unfavorable costs and maintain and improve the role of responsibility accounting.